Rare Case of Morquio Syndrome (Mucopolysaccharidosis Type IVA): Difficulties of Diagnostic Search and Management - Yulia P. Semschikova; Yurii A. Kozlov; Andrei B. Yakovlev; Vera M. Shinkareva; Tatyana V. Barzunova; Natalia I. Manjkova; Evgenii A. Balakirev (Педиатрическая фармакология)
Background. This clinical case is of practical interest due to the lack of epidemiological and clinical data in Russian Federation and worldwide, difficulties in diagnosis at the disease onset, as well as little experience in enzyme replacement therapy for mucopolysaccharidosis type IVA (MPS IVA).Clinical case description. MPS IV (Morquio syndrome) diagnosis at the age of 11 was based on typical progressive external signs such as thoracolumbar scoliosis, coxarthrosis with restriction of both active and passive movements. Enzymodiagnostics in dried blood spots has shown dramatic decrease of N-acetylgalactosamine-6-sulfatase activity — 0.01 μM/l/h specific to MPS IVA. Direct automatic sequencing of the GALNS gene has revealed pathogenic nucleotide variants in the compound heterozygous state: c.143T>G; p(Val48Gly) and c.697G>A; p.(Asp233Asn). That allowed us to establish MPS IVA diagnosis. Enzyme replacement therapy with elosulfase alpha was started according to the protocol. According to significant changes in the musculoskeletal system, the expected therapeutic effect (stabilization and no disease progression) can be achieved not earlier than after 8–12 months.Conclusion. Timely MPS diagnosis allows us to implement enzyme replacement therapy at the earliest possible time and thereby to avoid non-reversible complications of the disease itself.